Long-Term and Seasonal Trends in Global Wave Height Extremes Derived from ERA-5 Reanalysis Data - Alicia Takbash; Ian R. Young (Journal of Marine Science and Engineering, 2020)
A non-stationary extreme value analysis of 41 years (1979–2019) of global ERA5 (European Centre for Medium-Range Weather Forecasts Reanalysis) significant wave height data is undertaken to investigate trends in the values of 100-year significant wave height, <semantics><msubsup>Hs100</msubsup></semantics>. The analysis shows that there has been a statistically significant increase in the value of <semantics><msubsup>Hs100</msubsup></semantics> over large regions of the Southern Hemisphere. There have also been smaller decreases in <semantics><msubsup>Hs100</msubsup></semantics> in the Northern Hemisphere, although the related trends are generally not statistically significant. The increases in the Southern Hemisphere are a result of an increase in either the frequency or intensity of winter storms, particularly in the Southern Ocean.